2022
DOI: 10.1093/braincomms/fcac122
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative microseizure detection using a high-density micro-electrocorticography electrode array

Abstract: One-third of epilepsy patients suffer from medication-resistant seizures. While surgery to remove epileptogenic tissue helps some patients, 30–70% of patients continue to experience seizures following resection. Surgical outcomes may be improved with more accurate localization of epileptogenic tissue. We have previously developed novel thin-film, subdural electrode arrays with hundreds of microelectrodes over a 100–1000 mm2 area to enable high-resolution mapping of neural activity. Here, we used these high-den… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…It should also be noted that although studies of interictal activity from recordings in the epilepsy monitoring unit have indicated that HFOs coincident with interictal discharges, or "spikes," may be especially clinically valuable, we did not find sufficient instances of HFOs coincident with interictal discharges in our recordings to investigate their spatial scale in the present study 56,57 . Interestingly, our previous work also identified intraoperative microseizures in epilepsy patients using the same LCP‐TF μECoG arrays 35 . Thus, future work using implantable μECoG arrays to record for longer durations during presurgical monitoring under various states of consciousness will be essential to further understand the clinical relevance of microscale HFOs and their relationship over time to other interictal activity such as interictal discharges and microseizures.…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…It should also be noted that although studies of interictal activity from recordings in the epilepsy monitoring unit have indicated that HFOs coincident with interictal discharges, or "spikes," may be especially clinically valuable, we did not find sufficient instances of HFOs coincident with interictal discharges in our recordings to investigate their spatial scale in the present study 56,57 . Interestingly, our previous work also identified intraoperative microseizures in epilepsy patients using the same LCP‐TF μECoG arrays 35 . Thus, future work using implantable μECoG arrays to record for longer durations during presurgical monitoring under various states of consciousness will be essential to further understand the clinical relevance of microscale HFOs and their relationship over time to other interictal activity such as interictal discharges and microseizures.…”
Section: Discussionmentioning
confidence: 62%
“…56,57 Interestingly, our previous work also identified intraoperative microseizures in epilepsy patients using the same LCP-TF μECoG arrays. 35 Thus, future work using implantable μECoG arrays to record for longer durations during presurgical monitoring under various states of consciousness will be essential to further understand the clinical relevance of microscale HFOs and their relationship over time to other interictal activity such as interictal discharges and microseizures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations